KS02.7.A Impact of FET PET on multidisciplinary neurooncological tumor board decisions in patients with brain tumors. (5th September 2022) - Ceccon, G S; Werner, J; Ruge, M I; Goldbrunner, R; Celik, E; Baues, C; Deckert, M; Brunn, A; Büttner, R; Golla, H; Nogova, L; Schlamann, M; et al.
Abstract: Background: Following neurooncological treatment of brain tumors, neurooncologists are often confronted with equivocal MRI findings (e.g., treatment-related changes such as pseudoprogression, non-measurable contrast-enhancing lesions, T2/FLAIR signal alterations, pseudoresponse). Especially in Europe, amino-acid PET is increasingly integrated into multidisciplinary neurooncological tumor boards (MNTB) to overcome these diagnostic uncertainties. We evaluated the correctness of MNTB decisions, in which amino acid PET findings were taken into account. Material and Methods: In a single-university center study, we retrospectively evaluated 182 MNTB decisions of 154 patients with histomolecularly defined WHO grade 3 or 4 gliomas (n=123), including glioblastoma (n=80), anaplastic glioma (n=42), and gliosarcoma (n=1), or brain metastases (n=31) secondary to lung cancer, melanoma, breast cancer, or colorectal cancer presenting equivocal MRI findings following anticancer treatment. All patients underwent O -(2-[ 18 F]-fluoroethyl)-L-tyrosine (FET) PET imaging as an adjunct for decision-making. Additionally, the patients' clinical status, pretreatment, and conventional MRI findings were considered for decision-making. The presence of neoplastic tissue was considered if the mean FET uptake as assessed by tumor-to-brain ratios was > 2.0. MNTB decisions were validated using the neuropathological result in 42% (n=77) or clinicoradiologically in 58% (n=105). The diagnostic performance of MTNB decisions was evaluated using 2x2 contingency tables. Results: The validation of all 182 MNTB recommendations, which integrated FET PET in the decision-making process, were correct in 95% (sensitivity, 97%; specificity, 75%; positive predictive value, 96%). Due to tumor progression, MNTB recommendations prompted a treatment change in 88% (n=160 of 182 decisions). When FET PET findings suggested progressive disease (n=157), MNTB decisions were correct in 96% (positive predictive value, 97%). In 22 MNTB decisions with the recommendation to continue the current treatment regimen, 82% were correctly identified as treatment-related changes. Conclusion: FET PET seems to have a significant impact on MNTB decisions. A prospective evaluation of MNTB decisions with and without the integration of FET PET is warranted to define the added value of FET PET.